Decomposing Effects of Time on Task Reveals an Anteroposterior Gradient of Perceptual Decision Regions - Buchsbaum, Bradley R.; Erickson, Drew T.; Kayser, Andrew S. (PloS one, 2013)
In perceptual decision making, the selection of an appropriate action depends critically on an organism's ability to use sensory inputs to accumulate evidence for a decision. However, differentiating decision-related processes from effects of "time on task" can be difficult. Here we combine the response signal paradigm, in which the experimenter rather than the subject dictates the time of the response, and independent components analysis (ICA) to search for signatures consistent with time on task and decision making, respectively, throughout the brain. Using this novel approach, we identify two such independent components from BOLD activity related to a random dot motion task: one sensitive to the main effect of stimulus duration, and one to both the main effect of motion coherence and its interaction with duration. Furthermore, we demonstrate that these two components are expressed differently throughout the brain, with activity in occipital regions most reflective of the former, activity within intraparietal sulcus modulated by both factors, and more anterior regions including the anterior insula, pre-SMA, and inferior frontal sulcus driven almost exclusively by the latter. Consistent with these ICA findings, cluster analysis identifies a posterior-to-anterior gradient that differentiates regions sensitive to time on task from regions whose activity is strongly tied to motion coherence. Together, these findings demonstrate that progressively more anterior regions are likely to participate in progressively more proximate decision-related processes.